The impact of corporate social responsibility on poverty alleviation in mining areas in Tanzania: The case study of African Barrick Gold - Hauli, Steven Mugisha (Mzumbe university, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements of award of the degree of Masters of Business Administration in Corporate Management(MBA-CM) of Mzumbe University.